Igneous Rock Associations 21. The Early Permian Panjal Traps of the Western Himalaya - Shellnutt, J. Gregory (Geoscience Canada, 2016)
The Early Permian (290 Ma) Panjal Traps are the largest contiguous outcropping of volcanic rocks associated with the Himalayan Magmatic Province (HMP). The eruptions of HMP-related lava were contemporaneous with the initial break-up of Pangea. The Panjal Traps are primarily basalt but volumetrically minor intermediate and felsic volcanic rocks also occur. The basaltic rocks range in composition from continental tholeiite to ocean-floor basalt and nearly all have experienced, to varying extent, crustal contamination. Uncontaminated basaltic rocks have Sr–Nd isotopes similar to a chondritic source (ISr = 0.7043 to 0.7073; gNd(t) = 0 ± 1), whereas the remaining basaltic rocks have a wide range of Nd (gNd(t) = – 6.1 to +4.3) and Sr (ISr = 0.7051 to 0.7185) isotopic values. The calculated primary melt compositions of basalt are picritic and their mantle potential temperatures (TP ≤ 1450°C) are similar to ambient mantle rather than anomalously hot mantle. The silicic volcanic rocks were likely derived by partial melting of the crust whereas the andesitic rocks were derived by mixing between crustal and mantle melts. The Traps erupted within a continental rift setting that developed into a shallow sea. Sustained rifting created a nascent ocean basin that led to seafloor spreading and the rifting of microcontinents from Gondwana to form the ribbon-like continent Cimmeria and the Neotethys Ocean.